2021
DOI: 10.1002/jmv.27032
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of convalescent plasma therapy in severe COVID‐19 patients with persistent SARS‐CoV‐2 viremia

Abstract: This study aims to assess the efficacy and safety of convalescent plasma therapy (CPT) in COVID‐19 critically ill patients with protracted severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) RNAemia. A retrospective cohort study was conducted in intensive care unit (ICU). All patients with severe COVID‐19 pneumonia for whom RNAemia remained positive more than 14 days after onset of the infection were included and given CPT. The primary objective was to evaluate SARS‐CoV‐2 RNAemia 7 days (D7) after CPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Among the emerging therapies, Paxlovid has gained attention as a promising antiviral treatment with potential efficacy against SARS-CoV-2. Paxlovid, also known as PF-07321332/ritonavir, is an oral antiviral medication developed by Pfizer for the treatment of COVID-19 [139]. It functions as a protease inhibitor, targeting the SARS-CoV-2 virus's main protease (Mpro).…”
Section: Promising New Treatments Immune Therapies and Their Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the emerging therapies, Paxlovid has gained attention as a promising antiviral treatment with potential efficacy against SARS-CoV-2. Paxlovid, also known as PF-07321332/ritonavir, is an oral antiviral medication developed by Pfizer for the treatment of COVID-19 [139]. It functions as a protease inhibitor, targeting the SARS-CoV-2 virus's main protease (Mpro).…”
Section: Promising New Treatments Immune Therapies and Their Limitationsmentioning
confidence: 99%
“…Overall, the judicious use of generic drugs in host response treatments represents an essential component of the multifaceted approach to combatting COVID-19. Allergic reactions Improved clinical outcomes [157] Limited availability [134,158] Antiviral therapies Potential side effects (e.g., immune reactions, Reduction in disease severity [139] gastrointestinal symptoms, Improved clinical recovery [67] hypersensitivity reactions) [159] Paxlovid treatment Limited availability, side effects, effectiveness varies against specific strains of the virus Reduction in viral load, authorized for emergency use, complement to vaccination, alleviate symptoms [139,140] Immune modulators Risk of immune suppression Reduction in inflammation [67] Increased risk of secondary infections Improved outcomes in severe cases [159][160][161] Convalescent plasma therapy Allergic reactions Potential reduction in disease severity [162] Transfusion-related lung injury Improved outcomes when administered early [142] Novel immune therapies Potential risks (e.g., immune reactions) Novel therapeutic approaches [143] Thrombosis Potential for reducing inflammation [147] mRNA vaccines Cold storage requirements High efficacy in preventing COVID-19 [163] Limited global supply Induction of robust immune response [164] Possible adverse events (e.g., allergic reactions) Potential for reducing inflammation [165] Nanoparticle vaccines Development and manufacturing challenges Enhanced stability and shelf life [166] Need for further clinical validations Potential for targeted delivery [167] Cell-based therapies Limited availability Potential for personalized treatment [168] Immune rejection Multimodal immunomodulatory effects [169] Long-term safety concerns Potential for targeted delivery [170,171] Gene editing technologies Off-target effects Precise targeting of viral genetic material [172] Ethical considerations Potential for preventing viral replication [173] Limited clinical applications Enhanced stability and shelf life…”
Section: Promising New Treatments Immune Therapies and Their Limitationsmentioning
confidence: 99%
“…Convalescent plasma therapy has proven effective in treating patients infected by SARS‐CoV and MERS‐CoV [ 106 , 107 , 108 , 109 ]. Limited clinical data available for SARS‐CoV‐2 also suggested that this therapy was effective in reducing viral load and improving the survival of infected individuals [ 110 , 111 , 112 , 113 ]. As a result, convalescent plasma therapy was issued an emergency use authorization (EUA) and employed in China during the early stages of COVID‐19.…”
Section: Neutralizing Antibodies Targeting Cov S G...mentioning
confidence: 99%
“…Some studies suggest that antibodies are not enough to eliminate viruses, which is confirmed by the lack of a sharp drop in viral load post-seroconversion [ 61 ]. Monitoring the clinical outcome of convalescent plasma transfer therapy (CPTT) may be one approach to determining antibody efficacy [ 62 ]. CPTT trials in SARS-CoV-2 have yielded mixed results on the preventive role of neutralizing antibodies.…”
Section: Factors Involved In Inducing Long-term Immunity For Covid-19...mentioning
confidence: 99%
“…CPTT trials in SARS-CoV-2 have yielded mixed results on the preventive role of neutralizing antibodies. In case–control trials for severe SARS-CoV-2, CPTT initially showed encouraging results, with some research suggesting that earlier treatment was more effective [ 62 , 63 ]. SARS-CoV-1 patients were also found to benefit from early CPTT [ 64 ].…”
Section: Factors Involved In Inducing Long-term Immunity For Covid-19...mentioning
confidence: 99%